Pengaruh Kemudahan Pengajuan, Tingkat Pendapatan, Dan Jangka Waktu Pembiayaan Terhadap Keputusan Nasabah Mengajukan Pembiayaan Permodalan Nasional Madani (PNM) Mekaar Syariah (Survei Pada Nasabah Di Kecamatan Gandus) - Hermawati, Syintia; Hilda; Sania Riski, Oki (Lentera Jurnal Manajemen, 2025)
This study aims to analyze the influence of application convenience, income level, and financing term on customers’ decisions to apply for financing at Permodalan Nasional Madani (PNM) Mekaar Syariah (a survey of customers in the Gandus District). This research uses a quantitative descriptive approach with a survey research method, which involves collecting data on the research variables simultaneously. The sampling technique employed is the Slovin formula, based on a total population of 5,687 customers, resulting in a sample of 100 respondents. The data used is primary data collected through questionnaires distributed to the respondents. Data processing was conducted using SPSS version 26. Several tests were carried out, including normality and reliability tests, as well as classical assumption tests comprising normality, heteroscedasticity, multicollinearity, and linearity tests. Data analysis was conducted using multiple linear regression, and hypothesis testing was performed using the t-test and the coefficient of determination (R²). The results of the study show that application convenience significantly influences customers’ decisions to apply for PNM Mekaar Syariah financing in Gandus District, with a t-count value of 3.240, which is greater than the t-table value of 1.984. Income level also has a significant effect, with a t-count of 3.265, and financing term significantly influences the decision as well, with a t-count of 6.833. Therefore, application convenience, income level, and financing term are important factors in customers’ decisions to apply for PNM Mekaar Syariah financing in Gandus District.